Different sources of phosphorus in supplements for grazing cattle: inorganic phosphorus in plasma and osteocalcin - Lima, Beatriz da Silva; Silva, Lorrayny Galoro da; Coneglian, Sabrina Marcantonio; Lazzar , Claudia Mara; Serrano, Román David Castañeda; Branco, Antonio Ferriani (Pubvet, 2015)
The experiment was conducted to evaluate three non-conventional sources of phosphorus, triple superphosphate, monoammonium phosphate and rock phosphate Araxá in the diet of cattle grazing, and compare them with respect to dicalcium phosphate phosphorus concentration and serum osteocalcin. The experiment was conducted during the period from January 10 to May 5, 2009. The experimental design was completely randomized. We used 32 crossbred (zebu x taurine) with average initial weight of 347 kg and 21 months of age. Remained throughout the experiment (115 days) in pasture grass, star grass (Cynodon nlemfuensis Vanderyst), randomly allocated to four treatments that met the various additional sources of phosphorus: 1) dicalcium phosphate (BIC), triple superphosphate (SPT), monoammonium phosphate (MAP) and Phosphate Rock Araxá (FRA). Blood samples were collected 14 days after onset and 14 days before the end of the experiment. The concentrations of osteocalcin remained unchanged at 47.67 ng / mL and were similar between treatments. Phosphorus sources were effective in maintaining adequate levels of serum phosphorus (7.03 mg/100mL), considered as normal levels between 4 to 9 mg/100mL.
Keywords: gram-star; plasma parameters; ruminants